The Relation of Results to Objectives of Media Research – an Evaluative: Study of Research of al-Baath al-iilami Journal from 2007 to 2016 - الكعبي, رعد جاسم (ALBAHITH ALALAMI, 2017)
The main idea of this research is that the researcher believes that media research remains useless unless its goals and results are achieved by using the correct scientific tools. The researcher chooses 100 research papers of about 35% of the published ones, 10 of them are excluded because they are outside media. We use a simple and randomized sample including the three departments of media: journalism, television and radio journalism and public relations. The researcher adopts statistical methods such as Fay coefficient, correlation coefficient, Pearson correlation coefficient and straight line equation. The researcher uses an analytical form followed by analysis of content, them the scale. The results are found in 58 researches, while 31 of them have no results. The largest number of goals is in the field of journalism. The total number of goals reaches 212 and the total number of results is 463. The most important result of the research is that the goals achieved through the results by 50%, while 35% of these results are separated from the goals. In each research, the researcher finds that the goal rate reaches 3.6, and the results are 8.2. it is also found that the correlation between the set goals and the achieved results is very strong since the correlation coefficient between them is 0.88 which is reasonable.